Corrosion mechanism of Mo-W-ZrO2 cermet in molten steel. Issue 7 (May 2018) - Zhang, Jiu; Mei, Guohui; Xie, Zhi; Zhao, Shumao
Abstract: Mo-W-ZrO2 cermet has potential application in metallurgical industry. To optimize its corrosion resistance, the corrosion mechanism of Mo-35W-35ZrO2 cermet in molten steel has been investigated. Results showed that the corrosion resistance of the cermet mainly depended on the corrosion of its ceramic phase (ZrO2 ). The ceramic phase formed a ZrO2 layer (thickness: about 75 µm) on the cermet surface during the corrosion, while the metal phase (Mo-W) was corroded firstly. It was attributed to that the ceramic phase was corroded slowly by physical erosion of molten steel while the corrosion of the metal phase caused by its melting in molten steel was much faster. Meanwhile, the ZrO2 layer prevented molten steel from penetrating into cermet, lowering the melting corrosion rate of the metal phase to the physical erosion rate of the ceramic phase. As a result, the corrosion of the cermet reached dynamic equilibrium, which was corresponded to a small corrosion rate of about 0.05 mm/h. Therefore, the ZrO2 layer formation was the key to improve corrosion resistance, which might have important implication for solving the corrosion resistance problem of the similar cermet.